Test Amplification for REST APIs: Using "Out-of-the-Box" Large Language Models - Bardakci, Tolgahan; Demeyer, Serge; Beyazit, Mutlu (IEEE software, 2025)
Representational state transfer application programming interfaces (REST APIs) are an indispensable building block in today’s cloud-native applications. However, testing REST APIs is challenging because tests must be strong, readable, and exercise the boundary values of the REST API protocol.